1977
DOI: 10.1021/jm00215a014
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic agents. 4. Substituted phenoxypropanolamine derivatives as potential .beta.-adrenergic agonists

Abstract: A series of 1-(substituted phenoxy)-3-(tert-butylamino)-2-propanols in which the ring substituents were 3,4-dihydroxy (6f), 3- and 4-hydroxy (6g and 6h, respectively), 3-hydroxy-4-methylsulfonamido (6i), its 3,4-transposed isomer (6j), and 4-methylsulfonylmethyl (6k) was prepared and examined for beta-adrenergic agonist and/or antagonist properties. Two of these compounds, 6f and 6j, were potent beta-adrenoreceptor agonists in in vitro tests that measure a compound's ability to relax guinea pig tracheal smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

1977
1977
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 2 publications
1
21
0
1
Order By: Relevance
“…The results obtained by Kaiser et al (1977) using OM-N-t-butylnoradrenaline in guineapig atrial and tracheal preparations are in general agreement with those found in the present study. In contrast to the present results obtained with OM-isoprenaline in guinea-pig atria and in the cat heart in vivo (Dowd et al, 1977), Casagrande et al (1973) found that the compound was a partial agonist in rabbit atrial preparations.…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained by Kaiser et al (1977) using OM-N-t-butylnoradrenaline in guineapig atrial and tracheal preparations are in general agreement with those found in the present study. In contrast to the present results obtained with OM-isoprenaline in guinea-pig atria and in the cat heart in vivo (Dowd et al, 1977), Casagrande et al (1973) found that the compound was a partial agonist in rabbit atrial preparations.…”
Section: Discussionsupporting
confidence: 92%
“…To explain the similar pharmacological activity of the two classes of drugs, several hypotheses have been advanced (Ariens, 1967;Dangoumau, Barrans & Cotrait, 1973;Cromer, 1970;Barrett, 1972;Kaiser, Jen, Garvey, Bowen, Colella & Wardell, 1977;Ammon, Howe, Erhardt, Balsamo, Macchia, Macchia & Keefe, 1977;Ammon, Balsamo, Macchia, Macchia, Howe & Keefe, 1975;Petrongolo et aL, 1977;Macchia, Macchia & Martinelli, 1980;Lrvgren, Hedberg & Nilsson, 1980) on the mechanism through which the CH2-O-Ar portion of the class (II) agents can substitute for the single aromatic moiety (Ar) of the class (I) compounds in the drug-receptor interaction. On the basis of the observation that the insertion of the CH2-O group modifies the distances between the Ar group and the other active centers of the drug, it had been proposed (Ariens, 1967;Dangoumau et al, 1973) that complementary additional receptor areas could be involved in the drug-receptor interaction.…”
mentioning
confidence: 99%
“…Thus, oxypropanolamines have potent 3i-adrenoreceptor agonist or antagonist (168, 169) selectivity provided they have the absolute stereochemistry S (33,169). This is the same relative spacial orientation of the aromatic ring, hydroxy1 and amino groups found in the active adrenergic R-phenylethanolamines.…”
Section: Generally the S (+)-Enantiomers Have Only Weak 3-adrenergicmentioning
confidence: 89%
“…Several other catechols and related compounds with 3-adren ergic agonist activity involve a more profound structural modifi cation of the phenylethanolamine skeleton. The catecholoxypropanolamine 65^ which might be viewed as a congener of N-tertbutylnorepinephrine in which a 00Η 2 group is inserted between the catechol nucleus and the ethanolamine side chain, is a very potent 3-adrenoreceptor agonist; however, it has a marked selec tivity for cardiac rather than tracheobronchial muscle (33).…”
Section: Generally the S (+)-Enantiomers Have Only Weak 3-adrenergicmentioning
confidence: 99%
See 1 more Smart Citation